A Study How Do Community Care Providers Collaborate With Local Authorities and Emergency Response Teams During A Disaster Situation: A Literature Review - Riwayanti, Adinda Agus; Hutami, Citra Kirana; Azzahro, Nur Fauziah; Usraturrahmah, Usraturrahmah (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2024)
Introduction: The Unitary State of the Republic of Indonesia is a country located in a disaster-prone area due to geographical, geological, hydrological and demographic conditions that allow natural, non-natural and social disasters to occur. Therefore, the government passed Law Number 24 of 2007 concerning Disaster Management to disseminate information to the public regarding disaster management, provide protection to the community from every threat of disaster and ensure the implementation of disaster management. Methods: A systematic search was conducted against the Cochrane Database of Reviews, Google Scholar, PubMed, Scopus, Embase, and Web of Science. The keywords in this research are "natural disaster", "collaboration", and "community care". Results: After a thorough examination, only about seven were related to natural disasters, collaboration, and community awareness. Then, after a comprehensive examination, only about seven were related to natural disasters, collaboration and community care, as well as the importance of collaboration or partnerships between various health sectors. Conclusion: Disaster prevention and management is carried out in collaboration between the Government and health workers, NGOs, and community involvement. The role of the community is very important in efforts to increase awareness of disasters, requiring individuals who have a high level of resilience and can work under any risk, and the public health energy sector has a big role in disaster mitigation.